Case Report: First case of HIV, hepatitis B, hepatitis C, and Vibrio vulnificus coinfection - Zeng, Huimin; Guan, Jialong; Liang, Chudan; Wang, Yulong; Feng, Lizhi; Zhao, Han; Fan, Linjin; Yang, Xiaofeng; Pan, Nenglang; Wang, Zequn; He, Haolan; Chen, Zhimin; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Our patient, a 48-year-old man from Guangdong’s coastal region, worked selling and processing oysters and other seafood. He started experiencing swelling and pain in his left knee on October 4, 2022, and they got worse over time. The findings of mNGS test showed Vibrio vulnificus infection. The patient had AIDS, hepatitis A and hepatitis B concurrently. He was admitted to the hospital’s intensive care unit (ICU) for treatment as his symptoms worsened. We refrained from performing an amputation because the family members expressed a desire to keep the limb. The limb was managed with regular dressing changes, thorough debridement, wound closure, ongoing VSD drainage, and local antibiotic irrigation. The patient’s organ function eventually returned to normal, and the systemic infection got better. On November 1, the wound’s new granulation tissue had grown well and had gradually crept to cover 80% of the wound. The tissue’s blood flow had also improved, indicating a trend of growth and healing.